2008
DOI: 10.1186/1471-2350-9-42
|View full text |Cite
|
Sign up to set email alerts
|

Immunological profile in a family with nephrogenic diabetes insipidus with a novel 11 kb deletion in AVPR2 and ARHGAP4 genes

Abstract: BackgroundCongenital nephrogenic diabetes insipidus (NDI) is characterised by an inability to concentrate urine despite normal or elevated plasma levels of the antidiuretic hormone arginine vasopressin. We report a Japanese extended family with NDI caused by an 11.2-kb deletion that includes the entire AVPR2 locus and approximately half of the Rho GTPase-activating protein 4 (ARHGAP4) locus. ARHGAP4 belongs to the RhoGAP family, Rho GTPases are critical regulators of many cellular activities, such as motility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 20 publications
0
11
1
Order By: Relevance
“…Recently, there have been seven reports of the contiguous deletion of AVPR2 and ARHGAP4 genes in eight unrelated NDI patients [Schoneberg et al, 1999;Demura et al, 2002;Schulz et al, 2002;Broides et al, 2006;Dong et al, 2006;Fujimoto et al, 2008;Knops et al, 2008]. Our patients had significant ID and short stature, which distinguished them from previous reports (Table II and Fig.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…Recently, there have been seven reports of the contiguous deletion of AVPR2 and ARHGAP4 genes in eight unrelated NDI patients [Schoneberg et al, 1999;Demura et al, 2002;Schulz et al, 2002;Broides et al, 2006;Dong et al, 2006;Fujimoto et al, 2008;Knops et al, 2008]. Our patients had significant ID and short stature, which distinguished them from previous reports (Table II and Fig.…”
Section: Discussioncontrasting
confidence: 62%
“…Previous analysis of human ARHGAP4 revealed it to be highly expressed in hematopoietic cells [Tribioli et al, 1996], suggesting immunodeficiency to be a likely clinical sign of loss of ARHGAP4 function [Schoneberg et al, 1999;Broides et al, 2006;Fujimoto et al, 2008]. A recent study demonstrated that ARHGAP4 is more widely expressed.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Some earlier cases were analyzed in Daniel Bichet's laboratory in Montreal and reported previously [11]. Also, several cases have been reported separately before [12][13][14][15][16]. The AVPR2 and AQP2 genes are relatively small and all exons and intron-exon boundaries were sequenced with usual sequencing methods [12,17,18].…”
Section: Methodsmentioning
confidence: 99%